Research and conservation of the so-called Studentate at the Dominican Priory in Krakow - Bojęś-Białasik, Anna; Luboń-Radwańska, Agnieszka (Badania i konserwacja pomieszczeń tzw. studentatu w klasztorze dominikanów w Krakowie, 2022)
The topic of the article is architectural and conservation research in one of the rooms of the so-called studentate in the Dominican priory in Krakow, which brought very interesting and unexpected results. In a small room that served as a kitchen, elements of late-Gothic decoration were discovered, e.g. beamed ceiling, portal and large fragments of polychrome. The article describes the course of research and subsequent discoveries, each of which required individual decisions regarding the method of conservation and exposition. An important issue was the interpretation of the iconographic program of the polychrome and the analysis of the entire decoration in the context of architectural transformations and the supposed historical function of the room. Reference was also made to conservation and technical procedures related to, among others, the need to introduce a new load-bearing ceiling above the room.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 27-36
Keywords: architektura; Dominican priory; Kraków; research; conservation; wooden beam ceiling; polychromy; portal; klasztor dominikanów; badania; konserwacja; strop drewniany; polichromia